Ramona Quimby, age 8 - Cleary, Beverly; Tiegreen, Alan (New York : Morrow, 1981)
Presents the further adventures of the Quimby family as Ramona enters the third grade.
Elem. School Library Collection, June 2000.
Notable/Best Books (A.L.A.), March 2011.
School Library Journal, June 2000.
Horn Book, May 1996.
Elem. School Library Collection.
Newbery Medal/Honor.
Keywords: Family life -- Fiction; Schools -- Fiction; Family life -- Fiction; School stories; Family life -- Fiction; Schools -- Fiction; Newbery honor book; Kurzweil format available